2014
DOI: 10.1080/23273798.2014.942673
|View full text |Cite
|
Sign up to set email alerts
|

Contextual learning of L2 word meanings: second language proficiency modulates behavioural and event-related brain potential (ERP) indicators of learning

Abstract: New word learning occurs incidentally through exposure to language. Hypothesizing that effectiveness of contextual word learning in a second language (L2) depends on the quality of existing lexical semantic knowledge, we tested more and less proficient adult bilinguals in an incidental word learning task. One day after being exposed to rare words in an L2 (English) reading task, the bilinguals read sentences with the newly-learned words in the sentence-final position, followed by related or unrelated meaning p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
49
1
9

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(70 citation statements)
references
References 83 publications
(109 reference statements)
7
49
1
9
Order By: Relevance
“…In less proficient participants, the brain may not be able to register sufficiently well that the semantically related words are in fact related or that two semantically unrelated words are in fact unrelated, or both. This result replicates the larger N400 effect to incongruency in L2 in high-vs lower-proficiency bilinguals (Ardal, Donald, Meuter, Muldrew & Luce, 1990;Elgort, Perfetti, Rickles & Stafura, 2016). Note that here we only analysed the responses to the items that were familiar to the participants (although the result was also confirmed by an ad hoc analysis of all items).…”
Section: Semantic Similarity Effectssupporting
confidence: 74%
“…In less proficient participants, the brain may not be able to register sufficiently well that the semantically related words are in fact related or that two semantically unrelated words are in fact unrelated, or both. This result replicates the larger N400 effect to incongruency in L2 in high-vs lower-proficiency bilinguals (Ardal, Donald, Meuter, Muldrew & Luce, 1990;Elgort, Perfetti, Rickles & Stafura, 2016). Note that here we only analysed the responses to the items that were familiar to the participants (although the result was also confirmed by an ad hoc analysis of all items).…”
Section: Semantic Similarity Effectssupporting
confidence: 74%
“…As such, at the first stages of L2 word learning, the latency of N400 can be delayed in comparison to the canonical latency (e.g., in the 550-850 ms time window) as it was the case for the low proficiency learners in Ojima, Nakata, and Kakigi (2005). With respect to topography, newly learnt words can yield N400 effects over frontal electrode sites, instead of over the canonical centro-parietal sites (Elgort et al, 2015). Both the delayed latency and frontal distribution have been explained by lower proficiency and more effortful processing.…”
Section: Erps and L2 Researchmentioning
confidence: 99%
“…Previous studies demonstrated that ERPs may be sensitive to variables related to L2 instruction, such as proficiency (Elgort et al, 2015), individual differences (Tanner et al, 2013), immersion (Bowden et al, 2013) and the mid-and long-term effects of L2 classroom instruction (Soskey et al, 2016). Yet, while it is widely accepted in L2 instruction that an explicit focus on grammatical and lexical items yields the best learning effects (Spada & Tomita, 2010;Webb & Nation, 2017), remarkably few ERP studies sought to shed light on knowledge that has been acquired through either explicit or implicit instruction (i.e., the presence or absence of an attentional focus on L2 features).…”
Section: Erp Research and L2 Instructionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because readers' existing L2 vocabulary knowledge plays a role in the learning of new words (e.g., Elgort, Perfetti, Rickles, & Stafura, 2014), the participants' vocabulary test scores were included in the analyses of their explicit and implicit word knowledge as secondary interest predictors. The participants' vocabulary knowledge in English was measured using LexTALE (Lemhöfer & Broersma, 2012;www.lextale.com) and a vocabulary levels test (VLT) of controlled productive ability (Laufer & Nation, 1999).…”
Section: Participants' Vocabulary Knowledgementioning
confidence: 99%